2016
DOI: 10.1155/2016/2420568
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Duration of Basic Life Support Training on the Learners’ Cardiopulmonary and Automated External Defibrillator Skills

Abstract: Background. Basic life support (BLS) training with hands-on practice can improve performance during simulated cardiac arrest, although the optimal duration for BLS training is unknown. This study aimed to assess the effectiveness of various BLS training durations for acquiring cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) skills. Methods. We randomised 485 South Korean nonmedical college students into four levels of BLS training: level 1 (40 min), level 2 (80 min), level 3 (120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…This accords with previous research on community response teams . Confidence and duration of training also lead to an increased likelihood of a willingness to use an AED when required …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This accords with previous research on community response teams . Confidence and duration of training also lead to an increased likelihood of a willingness to use an AED when required …”
Section: Discussionsupporting
confidence: 85%
“…in a systematic review of available studies found many of the same barriers and facilitators to early access to defibrillation as this original research . Another study found a direct link between confidence and duration of training leading to increased likelihood of a willingness to use an AED when required . Kitamura et al .…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have reported that relatively short durations of handsonly CPR training are effective in the acquisition and retention of CPR skills [8,17]. In contrast, other studies have reported that longer durations of hands-on practice improve the acquisition of CPR skills after training [18,19]. Our results suggest that, although hands-only CPR may be easier to learn and perform than conventional CPR, it is difficult for lay rescuers to maintain their CPR skills over time.…”
Section: Discussionmentioning
confidence: 99%
“…This dataset (available in the accompanying Supplementary Excel Spreadsheet file) summarises, in 28 tables, the psychomotor skill data extracted from 31 primary peer-reviewed articles that met the inclusion criteria for the related systematic review [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. The psychomotor skills for which data were extracted and reported were: compression rate, compression depth, duration of interruptions to compressions, chest recoil, hand placement, proportion of adequate or ’correct’ compressions, ventilation volume, compression-to-ventilation ratio, duty cycle and overall skills.…”
Section: Datamentioning
confidence: 99%